The impact of environmental and health messaging, pulse prevalence, and filtering tools on pulse-based food choice and nutrient profiles: a randomized online experiment - Gustafson, Christopher R.; Gitungwa, Henriette; Rose, Devin J. (Frontiers in Sustainable Food Systems, 2025)
IntroductionPulses deliver beneficial nutrient profiles together with low environmental impacts, yet pulse consumption in the US is below recommendations.MethodsThe aim of this study was to examine the impact of three interventions on pulse choices in a complex product environment: (1) the percentage of pulse products, (2) health/environment messaging, and (3) a pulse filter. We conducted a pre-registered experiment on participants’ food choices in an online retail-style setting with a representative sample of over 6,400 US adults. The choice environment featured six food categories containing 50 products each. The intervention arms examined: (1) the proportion of pulse foods in the choice environment (10% vs. 20%), enhancing awareness of the benefits of pulses at the point of decision (health and/or environmental messaging), and reducing search costs for pulse products in complex retail environments via a pulse filter. We analyzed the data by calculating the proportion of pulse products chosen in each condition and by performing logistic regression on the choice of pulse products. Independent variables were the experiment conditions and food product categories, with covariates that adjusted for demographics and knowledge, beliefs, and consideration of health and environmental priorities.ResultsResults showed that messaging alone and increasing the prevalence of pulse products had modest but significant impacts [range of adjusted odds ratios (95% confidence intervals): 1.35 (1.00, 1.83) to 2.91 (2.26, 3.75)]. Providing a pulse filtering option markedly increased pulse product choices [9.13 (7.07, 11.80) to 20.48 (15.98, 26.24)].DiscussionCombining messaging with filtering resulted in larger relative increases in pulse choices, suggesting that decreasing product search and identification costs may be an important component of interventions. We found that promoting the choice of pulse foods, which provides important nutritional and environmental benefits, can improve the nutrient content of foods selected.